INVESTIGATION OF VOT AS AN ACOUSTIC FEATURE OF CONSONANTS IN STRESSED SYLLABLE IN ADULTS WITH DOWN SYNDROME - Khaloueipour, Nasim; Abolhasanizedeh, Vahideh; Shafiei Moghadam, Farshad (PEOPLE: International Journal of Social Sciences, 2017)
Down syndrome (DS) is the most common genetic impairment, which is caused by the copy of an additional chromosome 21. In the case of Down syndrome, physical and health disorders, intellectual disabilities, and neuron-psychological defects are undeniable. The purpose of this research is to investigate acoustically voice onset time (VOT) in stressed and unstressed positions in adults with Down syndrome. For this purpose, two minimal pairs (tɒbeʃ/tɒb-eʃ – tɒpeʃ/tɒp-eʃ) are considered. In this study, 18 research participants with Down syndrome (nine boys with mean of ages 28, and nine girls with mean of ages 30), were asked to pronounce tɒbeʃ/tɒb-eʃ and tɒpeʃ/tɒp-eʃ and repeat them four times. The participants' productions were recorded using a Shure microphone and analyzed by PRAAT (6.0.22) software. The results revealed that VOT mean of [b, p] in stressed syllable significantly differs from that in unstressed syllable in adults with Down syndrome.